Quality scoreboard: a proposal - Domingues, José Pedro Teixeira (2014)
Purpose: The assessment of “macroquality” or the assessment of the degree to which the quality practices are implemented in a country or a region should not be only based on “tangible” indicators such as the number of certified companies according to the ISO 9001 or ISO 14001 standards, or others. By adopting only these two indicators (or similar ones) a large amount of companies, those ones that are not certified, are not considered when assessing the “macroquality”. Less tangible features, such as the number of persons trained in quality management or the number of members of quality management associations among other features, contribute themselves and seem appropriate to assess the level of “macroquality”. This paper intends to report a “macroquality” index that is composed by tangible and less tangible features, concerning the quality practices implementation concept- The Quality Scoreboard. Design/methodology/approach: An expert’s panel was conducted with the aim of evaluating a set of several indicators that could be used to assess and to monitor the “macroquality” level of a country. Nine tangible indicators were proposed and been analysed by the experts’ panel according to an importance scale (1 to 5). Additionally, the experts were encouraged to propose other indicators that could reflect the quality state-of-the-art of a country or region. Findings: Experts find that tangible indicators are not enough to express the level of “macroquality”. According to the results, less tangible features should be considered too. A total of 43 indicators were suggested by the experts. Among them, the following suggested indicators should be highlighted: the number of persons trained in quality management, the number of members of quality management associations, the number of quality related courses at the universities and the number of certified auditors. Based on the survey results a Quality Scoreboard was developed. Originality/value: As far as we were able to find out this is the first attempt to develop a Quality Scoreboard, as it had been already done to innovation. This new approach allows one to characterize the quality state-of-the-art of a region, based on a set of potential “quality indicators”. Furthermore, the results provide an additional important contribution to the worldwide study of quality approaches diffusion and evolution.